Evaluación de la relación entre la confianza en los médicos veterinarios y la satisfacción de los usuarios del servicio quirúrgico en una clínica veterinaria docente de Lima, Perú - Chipayo Gonzales, Ysaac Ruben (2025)
The aim of this study was to determine the relationship between trust in veterinary practitioners of the surgical service provided at the Small Animal Clinic of the Universidad Nacional Mayor de San Marcos (CAMe-FMV-UNMSM) and the satisfaction of the clinic's patient owners. The study was carried out between June and December 2021 by applying a questionnaire to 109 clients. Four dimensions were considered for the trust variable and three dimensions for the satisfaction variable. The Kendall test was used (p<0.05). It was found that users considered the professionals trustworthy in 92.7% and that they were satisfied with the service in 92.7%. The Kendall Tau b correlation coefficient was 0.57 between the variables trust and satisfaction. It is concluded that the relationship between trust in veterinarians and the satisfaction of users of the CAMe-FMV-UNMSM surgical service is significant, moderate and direct.